2009
DOI: 10.1002/pro.55
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a G protein‐coupled receptor for structural studies: Stabilization of the BLT1 receptor ground state

Abstract: Structural characterization of membrane proteins is hampered by their instability in detergent solutions. We modified here a G protein-coupled receptor, the BLT1 receptor of leukotriene B 4 , to stabilize it in vitro. For this, we introduced a metal-binding site connecting the third and sixth transmembrane domains of the receptor. This modification was intended to restrain the activation-associated relative movement of these helices that results in a less stable packing in the isolated receptor. The modified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Furthermore, 7A8 bound the second extracellular loop of mBLT1 ( Fig 3 ), and did not affect the LTB 4 binding and intracellular signaling ( S1 Fig ). These results are consistent with previous studies showing that the transmembrane domains III, V and VI of BLT1 are involved in the LTB 4 binding [ 64 , 65 , 66 ]. Our data suggests that 7A8 mAb will be a very useful tool to clarify the physiological and pathophysiological functions of BLT1 in various disease models by quickly eliminating BLT1-expressing cells without inducing the compensatory gene expression caused by BLT1 deficiency.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, 7A8 bound the second extracellular loop of mBLT1 ( Fig 3 ), and did not affect the LTB 4 binding and intracellular signaling ( S1 Fig ). These results are consistent with previous studies showing that the transmembrane domains III, V and VI of BLT1 are involved in the LTB 4 binding [ 64 , 65 , 66 ]. Our data suggests that 7A8 mAb will be a very useful tool to clarify the physiological and pathophysiological functions of BLT1 in various disease models by quickly eliminating BLT1-expressing cells without inducing the compensatory gene expression caused by BLT1 deficiency.…”
Section: Resultssupporting
confidence: 94%
“…After β 1 AR-JM3 was constructed, Martin et al 38 demonstrated a significant improvement in the thermostability of the leukotriene B 4 receptor BLT1 by engineering a Zn 2+ -bridge that was designed to prevent the formation of the activated receptor R*. This was achieved by the introduction of two His residues at the cytoplasmic ends of H3 and H6 that, in combination with other co-ordinating side chains, was able to bind Zn 2+ with high-affinity.…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of this strategy for the thermostabilisation of GPCRs rests on the observation that the R* conformation is invariably less stable than the R state 41 . Therefore, in theory, it should be possible to thermostabilise any GPCR by engineering in a Zn 2+ -bridge to prevent the formation of R*, although the thermostability of these engineered β 2 AR Zn 2+ -bridge mutants, only the stability of BLT1 was measured 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The concept of changing non-consensus residues to consensus residues has been successful in stabilizing soluble proteins 53 and should perhaps be tested more extensively for membrane proteins, given the success with the b2-adrenergic receptor. Recently, Baneres and coworkers 54 presented an entirely new way to engineer stability and conformational rigidity into a GPCR. In this work, a Zn 2þ binding site was introduced into the leukotriene receptor, BLT1, by the introduction of three histidine residues predicted to be close in space based on a homology model (see Fig.…”
Section: More Rational Protein Engineering Approachesmentioning
confidence: 99%
“…To restrain transmembrane helices 3 and 6 (light blue), Baneres and coworkers engineered a Zn 2þ binding site by introducing three His residues at positions predicted to be close in space. 54 One residue in TM3, Val119, and two residues in TM6, Arg218, and Thr219 were selected from the BLT1 model to mutate to histidine. The figure shows a model with the three side chains replaced with histidines for illustration only.…”
Section: Expressionmentioning
confidence: 99%